PENGARUH PENAMBAHAN RAGI TAPE DAN WAKTU FERMENTASI TERHADAP KARAKTERITIK PULPA BIJI KAKAO - Agus Ariefta, Gede; Ganda Putra, Gusti Putu; Anggreni, A.A.M. Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 2 (2016): Juni)
urpose of this study were 1). assessing the effect of tape inoculum addition and fermentation time on the characteristics of the cacao bean pulp, 2). determine the treatment could provide an indicator in the best process of destruction of cacao bean pulp. This study used randomized block design (RAK) with two factor. The first factor was the concentration of tape inoculum addition that consists of 5 levels ie 0% (no control), 0.5%, 1%, 1.5% and 2%. The second factor was the time of fermentation which consists of 5 levels namely 1 day, 2 days, 3 days, 4 days and 5 days. The experiments were grouped into 2 groups based on the time of implementation, in order to obtain 50 units experiment. The result showed that the treatment of tape inoculum addition had very significant effect on pH, total acid, pectin content and reducing sugar of cocoa bean pulp. The treatment of fermentation time had very significant effect on pH and reducing sugar of cocoa bean pulp, but did not affect on the total acid,and pectin content. Interaction of the treatmens had no effect on pH, total acid, pectin content, reducing sugar of cocoa bean pulp. The treatment of 2% tape inoculum addition and 4 days fermentation was the best treatment to destroy pulp during cacao bean pulp fermentation with the best characteristics was 2.10% pectin content, reducing sugar of 0.70%, total acid of 0.50 meq NaOH / g, and pH of 3.90. Keywords:cacao, fermentation, tape inoculum.
Keywords: 96,